The effect of testosterone on mood and well‐being in men with erectile dysfunction in a randomized, placebo‐controlled trial. (15th March 2013) - Spitzer, M.; Basaria, S.; Travison, T. G.; Davda, M. N.; DeRogatis, L.; Bhasin, S.
Summary The relationship between testosterone, well‐being and mood is poorly understood. We investigated the effect of testosterone supplementation on mood, well‐being, and self‐reported health in men with erectile dysfunction (ED) and low serum testosterone levels. This was a randomized, double‐blind, placebo‐controlled trial (ClinicalTrials.gov registration number NCT00512707), in which 140 men, 40–70 years, with ED and low serum testosterone levels were first optimized on sildenafil alone for 3–7 weeks and then randomized to receive either sildenafil plus testosterone gel (n = 70) or sildenafil plus placebo (n = 70) gel for 14 weeks. Using multiple imputations and generalized linear regression, we compared psychological changes in well‐being, evaluated by the Psychological General Well‐Being Index, and mood, evaluated by Derogatis Affects Balance Scale. Mood and well‐being scores were similar between the two groups at baseline and did not substantially change during the administration of sildenafil or after randomization to testosterone. Our findings show that the addition of testosterone to sildenafil in men with ED and low serum testosterone levels was not associated with improvement in either well‐being or mood.